Dynamics of Imidazolium Ionic Liquids from a Combined Dielectric Relaxation and Optical Kerr Effect Study: Evidence for Mesoscopic Aggregation - Turton, David A; Hunger, Johannes; Stoppa, Alexander; Hefter, Glenn; Thoman, Andreas; Walther, Markus; Buchner, Richard; Wynne, Klaas (Journal of the American Chemical Society, 2009)
We have measured the intermolecular dynamics of the 1,3-dialkylimidazolium-based room-temperature ionic liquids (RTILs) [emim][BF4], [emim][DCA], and [bmim][DCA] at 25 °C from below 1 GHz to 10 THz by ultrafast optical Kerr effect (OKE) spectroscopy and dielectric relaxation spectroscopy (DRS) augmented by time-domain terahertz and far-infrared FTIR spectroscopy. This concerted approach allows a more detailed analysis to be made of the relatively featureless terahertz region, where the higher frequency diffusional modes are strongly overlapped with librations and intermolecular vibrations. Of greatest interest though, is an intense low frequency (sub-α) relaxation that we show is in accordance with recent simulations that have reported mesoscopic structure arising from aggregates or clusters—structure that explains the anomalous and inconveniently high viscosities of these liquids.